1997
DOI: 10.1097/00002508-199709000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gabapentin on Neuropathic Pain

Abstract: Gabapentin may be a useful adjunct for treating neuropathic pain with a minimum of side effects. Particular advantage may be gained with the use of this drug for postherpetic neuralgia and direct peripheral nerve injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
8

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(96 citation statements)
references
References 11 publications
1
87
0
8
Order By: Relevance
“…Recent preclinical studies suggest a role for the ␣ 2 ␦ subunit in neuropathic pain processing. Gabapentin, an anticonvulsant drug found to be effective against clinical neuropathic pain states (Mellick et al, 1995;Rosner et al, 1996;Mellick and Mellick, 1997;Rosenberg et al, 1997;Backonja et al, 1998;Rowbotham et al, 1998), also exerts a spinal action in preclinical neuropathic pain models (Hwang and Yaksh, 1997;Abdi et al, 1998) and yet lacks general analgesic properties (Field et al, 1997). Gabapentin binds with high affinity to the ␣ 2 ␦ subunit in vitro (Gee et al, 1996).…”
Section: Abstract: ␣ 2 ␦ Calcium Channel Subunit; Peripheral Nerve Imentioning
confidence: 99%
“…Recent preclinical studies suggest a role for the ␣ 2 ␦ subunit in neuropathic pain processing. Gabapentin, an anticonvulsant drug found to be effective against clinical neuropathic pain states (Mellick et al, 1995;Rosner et al, 1996;Mellick and Mellick, 1997;Rosenberg et al, 1997;Backonja et al, 1998;Rowbotham et al, 1998), also exerts a spinal action in preclinical neuropathic pain models (Hwang and Yaksh, 1997;Abdi et al, 1998) and yet lacks general analgesic properties (Field et al, 1997). Gabapentin binds with high affinity to the ␣ 2 ␦ subunit in vitro (Gee et al, 1996).…”
Section: Abstract: ␣ 2 ␦ Calcium Channel Subunit; Peripheral Nerve Imentioning
confidence: 99%
“…Systemic therapies of choice are tricyclic antidepressants [40]. anticonvulsant agents [41], alpha blocking agents [42], and systemic lidocaine [43].…”
Section: Discussionmentioning
confidence: 99%
“…32,33 A summary of selected published studies on this subject appears in Table 2. [27][28][29][30][31][32][33] Morello et al demonstrated that there is no statistically significant difference between amitriptyline and gabapentin in the treatment of diabetics with peripheral neuropathic pain, as measured by pain scales and global pain scores. 34 In this study, 21 diabetic patients with stable glycemic control received either gabapentin or amitriptyline for 6 weeks and then crossed over to the other arm of therapy for 6 additional weeks, with a 1-week wash-out period between therapies.…”
Section: Gabapentin In the Treatment Of Pain Syndromes Peripheral Nementioning
confidence: 99%